MEDIA AND MUSHARRAF: A MARRIAGE OF CONVENIENCE - Iqbal, Zafar (European Scientific Journal, ESJ, 2012)
Media have never been consistently free in Pakistan. Different regimes used legal and constitutional means to control the media from public debate and criticism. In it over sixty-two years of history, Pakistan has been ruled by military more than the civilian. Media in Pakistan usually face threats, violence, economic pressure, etc. The country’s laws have been used against journalists. Poor literacy, urban orientation of the media, and the high price of newspapers are detrimental factors for the under development of media in Pakistan. Beside these barricades, one can now easily notice a shift from the centralized broadcasting to an open competition broadcast system in Pakistan, enabling the audience to enjoy more power of selective exposure. All governments including the military say high about the media freedom but often do the thing other way round when media criticize the government. However, during the Musharraf military and civil regime for about nine year, media were operated in a mixed character. This paper sheds some light on media and politics during General (r) Pervez Musharraf regime.